2012
DOI: 10.1152/ajprenal.00116.2012
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial sodium channel δ-subunit: new notes for an old song

Abstract: Amiloride-sensitive epithelial Na(+) channels (ENaCs) can be formed by different combinations of four homologous subunits, named α, β, γ, and δ. In addition to providing an apical entry pathway for transepithelial Na(+) reabsorption in tight epithelia such as the kidney distal tubule and collecting duct, ENaCs are also expressed in nonepithelial cells, where they may play different functional roles. The δ-subunit of ENaC was originally identified in humans and is able to form amiloride-sensitive Na(+) channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 101 publications
2
53
0
2
Order By: Relevance
“…Thus impairment of the Na-K-ATPase during ALI not only prevents resolution of pulmonary edema but also exacerbates its formation. Recently, a fourth subunit of ENaC, termed ␦ ENaC, was discovered and proved to have unique biophysical and pharmacological properties compared with ␣ ENaC (76,112). Importantly, in human primary nasal epithelial cells (humans express ␦ ENaC) up to 40% of amiloride-sensitive sodium transport is associated with ␦ ENaC (9), and alterations in nasal potential may be indicative of Na ϩ channel dysfunction in ALI (146).…”
Section: L669 Acute Lung Injury and Barrier Dysfunctionmentioning
confidence: 99%
“…Thus impairment of the Na-K-ATPase during ALI not only prevents resolution of pulmonary edema but also exacerbates its formation. Recently, a fourth subunit of ENaC, termed ␦ ENaC, was discovered and proved to have unique biophysical and pharmacological properties compared with ␣ ENaC (76,112). Importantly, in human primary nasal epithelial cells (humans express ␦ ENaC) up to 40% of amiloride-sensitive sodium transport is associated with ␦ ENaC (9), and alterations in nasal potential may be indicative of Na ϩ channel dysfunction in ALI (146).…”
Section: L669 Acute Lung Injury and Barrier Dysfunctionmentioning
confidence: 99%
“…Because the molecular basis for the distinct sodium conductances detected in native respiratory epithelial cells has not been identified, the possible contribution of δ-ENaC-generated currents to the net sodium transport is of a particular interest. However, the fact that δ-ENaC in rodents is a pseudogene hinders the development of experimental animal models, thus in vitro approaches are currently the most promising to elucidate the physiological function of the ion channel [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has four subunits: α ENaC, β ENaC, γ ENaC, and δ ENaC. It has been reported that the most prominently expressed ENaC subunit in the human brain cortex is δ, while very low expression levels of α, β, and γ have been detected (Waldmann et al 1995;Yamamura et al 2004;Giraldez et al 2007Giraldez et al , 2012. Additionally, expression of δ ENaC is restricted to neurons (Giraldez et al 2007).…”
Section: Introductionmentioning
confidence: 99%